Pelatihan Pembuatan Gula Merah Cair dan Pemasaran E-Commerce di Desa Tapango Kecamatan Tapango Kabupaten Polewali Mandar - Rufaida, Erty Rospyana; Asnidar (Belalek, 2023)
Community Service with the title “Pelatihan Pembuatan Gula Merah Cair dan Pemasaran E-Commerce di Desa Tapango Kecamatan Tapango Kabupaten Polewali Mandar”. This activity is based on the conditions of making brown sugar whose manufacturing and marketing processes are still simple, very simple. Through this community service activity, training will be given on procedures for developing brown sugar products and the online marketing process through e-commerce. Product development is carried out by providing training to the public about processing liquid brown sugar so that the brown sugar they market is not only in simple form, but the product can be further developed and will have an impact on higher selling value (economic value). With a high selling value, it will have an impact on brown sugar sales revenue which will increase. Furthermore, after providing training on how to manage liquid brown sugar until it reaches the stage of packaging the product properly so that the liquid brown sugar is ready to be marketed. After product development, they will also be taught about online marketing strategies through various social media applications such as Facebook and Instagram. Apart from that, there is also online marketing in one of the number one online shop applications in Indonesia, namely the Shopee application. In this way, it is hoped that the brown sugar products they produce will not only be marketed on a local scale but will be able to compete on the national scale market.